Price Forecasting Using Neural Networks (for example, analysis of the futures on the RTS index) - V. G. Keschan; E. A. Skryabin (Ученые записки Российской академии предпринимательства, 2021)
This article focuses on aspects of preparation data and conducted experiment of training the neural network on the RTS Index futures, with Neuro-Fuzzy Designer (Matlab) program package. As a result, it concluded that neural networks have a high potential as a tool in forecasting prices.